How internal control system affects risk management: the case of commercial banking - Reza Zandi, Gholam; Hui, Yao (Opción, 2019)
This research explores the concept of the effect of Internal Control System on Risk Management in Malaysian Commercial Banking sector via a quantitative research method through conduction of primary data collection. The finding attained in this study revealed that internal control is the basic and most important risk management practices for banks and financial institutions and risk can be controlled by monitoring and reviewing the internal activities. In conclusion, most aspects of the internal control system have been taken and implemented by commercial banks in Malaysia, but with the exception on the regular review and improvement on the system